'An Injurious Effect on the Neighbourhood': Narratives of Neighbourhood Decline and Racialised Class Identities in Late Nineteenth-Century San Francisco. Issue 1 (2nd January 2018) - Jewell, Joseph O.
Abstract: Spatial narratives of neighbourhood decline – stories about threats to neighbourhood resources – were crucial in reinscribing racialised class boundaries in the late nineteenth century. In 1894, white middle-class property owners in San Francisco's Powell Street district protested the Board of School Directors' decision to relocate the city's only Chinese public school to a condemned building in their neighbourhood, leading to the renovation of the school's existing structure within Chinatown and new efforts to restrict both Chinese and Japanese urban settlement. I analyse this event to show the importance of space for the race–class intersection. Protesters described the financial, social and moral costs of living near a Chinese school, thereby establishing racial criteria for middle-class identity and mobility. Theories of racial space must consider discursive links between race, class and space because spatial narratives that reproduce economic dominance over racial minorities help to maintain the racial order.